Fundamentos para um direito do trabalho da integração a partir das experiências do Mercado Comum do Sul e União Européia - Cynthia Lessa da Costa (2019)
The end of the European War (1918-1945) launched a new era in which States borders startedfading. Although these borders never represented limits to the movement of corporations, theflow of workers was completely controlled by the national states will, until then, when newlegal structures reconfigured the relations between States under the invention of sharedsovereignty driven by the phenomenon of region building, a redrawing of the inter-Staterelations that creates supranational entities to which part of the powers and loyalties, that weredevoted exclusively to the national state, should be transferred, breaking some of the mysticsof the modern State, in particular, the autonomy to rule upon its territory without interference.This thesis argues that this context requires the construction of the Law under a new rationalitywhich, it is claimed, must spread to all legal branches of law applicable to this new legal space.Counterpointing the pillars of this claimed Integration Law with the rationality that carries outthe classic (modern) Labour Law, one can conclude towards its incompatibility with the newparadigm. Accordingly, this thesis proposes some foundations to build an Integration LabourLaw under the framework of the theories by Kühnhardt, Wolfgang Deutsch and Álvares daSilva